Perbandingan Efektivitas Penurunan Berat Badan pada Pasien Gastric Bypass & Gastric Sleeve RS EMC Alam Sutera 2021-2023 - Agnes Caitlyn Kapito; Suhuyanly, Nella; Arsita, Elli (Jurnal MedScientiae, 2025)
Background: Obesity is a growing global health issue. According to WHO data from 2022, one in eight people worldwide lives with obesity, and 21.8% of the adult population in Indonesia suffers from obesity. Bariatric surgery approaches, typically gastric sleeve and gastric bypass have become one of the options to address this problem. Objective: This study aims to compare the efficacy of weight loss in patients undergoing bariatric surgery at EMC Alam Sutera Hospital between 2021 and 2023. Methods: This research is an analytical descriptive study with a retrospective cohort approach. The sample size was determined using purposive sampling technique, with a total of 70 samples. Data were obtained from medical records at EMC Alam Sutera Hospital from 2021 to 2023. Results: Out of 70 patients with an average age of 37.1 years, 88.6% were female and 11.4% were male. No significant differences were found in the variables (p > 0.05). The average weight loss for both surgeries was 5.9 kg, with no statistically significant difference. A higher correlation was observed for gastric sleeve (0.996) compared to gastric bypass (0.985). Conclusion: It can be concluded that both gastric bypass and gastric sleeve are proven effective in reducing weight. Both methods show strong correlations, although gastric sleeve has a slightly higher correlation. There is no significant difference in effectiveness between the two methods, with p > 0.05 for all measured parameters.